2014
DOI: 10.1155/2014/714749
|View full text |Cite
|
Sign up to set email alerts
|

mAb CZP-315.D9: An Antirecombinant Cruzipain Monoclonal Antibody That Specifically Labels the Reservosomes ofTrypanosoma cruziEpimastigotes

Abstract: Reservosomes are large round vesicles located at the posterior end of epimastigote forms of the protozoan Trypanosoma cruzi, the etiological agent of Chagas disease. They are the specific end organelles of the endocytosis pathway of T. cruzi, and they play key roles in nutrient uptake and cell differentiation. These lysosome-like organelles accumulate ingested macromolecules and contain large amounts of a major cysteine proteinase (cruzipain or GP57/51 protein). Aim of this study was to produce a monoclonal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…This hydrolase is synthesized as a zymogen of 57 kDa, from which the N-terminal pro-domain is removed autocatalytically, to generate the active enzyme (51 kDa) [ 57 ]. Once cruzipain is processed in the endoplasmic reticulum/Golgi complex, it is delivered to reservosomes, which only contain mature cruzipain [ 40 ]. Given the potential importance of TcAP1-γ in vesicular traffic from the TGN—including reservosome-bound traffic in T .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This hydrolase is synthesized as a zymogen of 57 kDa, from which the N-terminal pro-domain is removed autocatalytically, to generate the active enzyme (51 kDa) [ 57 ]. Once cruzipain is processed in the endoplasmic reticulum/Golgi complex, it is delivered to reservosomes, which only contain mature cruzipain [ 40 ]. Given the potential importance of TcAP1-γ in vesicular traffic from the TGN—including reservosome-bound traffic in T .…”
Section: Resultsmentioning
confidence: 99%
“…cruzi –we investigated whether the transport of cruzipain to reservosomes was affected in TcγKO parasites. First we analyzed the expression of cruzipain in TcγKO cells using an anti-cruzipain antiserum that recognizes both the unprocessed and mature form of this enzyme [ 40 ]. Western blot analysis showed that the cruzipain zymogen form (57 kDa) was recognized by the anti-cruzipain antiserum in both WT and in TcγKO epimastigotes, although the latter had increased zymogen levels ( Fig 6A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For co-localization of CZP/transferrin-AlexaFluor-633, the samples incubated with CZP-315.D9 mAb (at 50 μg/ml) [40], were washed three times in PBS and then incubated with a secondary goat anti-mouse-AlexaFluor-488 antibody (1:600 in incubation buffer). For the co-localization with CZP/albumin-AlexaFluor-488, the samples were incubated with CZP-315.D9 mAb and then incubated with a secondary goat anti-mouse-AlexaFluor-594 antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Immunolocalization: It was reported that T. cruzi epimastigotes use two endocytic vesicles; cytostome/ cytopharynx complex and the flagellar pocket membrane, to ingest extracellular macromolecules to be stored in reservosomes [122] . Using a monoclonal antibody (mAb) against recombinant CRZ localized a 50 kDa protein in reservosomes [123] . Later, endocytosis was visualized in intracellular amastigotes, and the digested extracellular macromolecules were stored in CRZ-positive lysosome-related structures (LRSs).…”
Section: Trypanosoma Spp American Trypanosomiasis Cysteine Proteinasmentioning
confidence: 99%